PENGALAMAN PERAWAT DALAM MENGANTISIPASI FLUKTUASI PASIEN DI INSTALASI GAWAT DARURAT RUMAH SAKIT UMUM IMELDA PEKERJA INDONESIA (RSU IPI) MEDAN - Hamonangan Damanik; Elisa Rahman Rambe; Ester Mei Frida (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2025)
The Emergency Department (IGD) is a part of the hospital that provides initial services to sick and injured patients. Overcrowding in the ER can result from a shortage of nursing staff, the number of patients waiting to be seen, a shortage of beds, delays in treating or assessing patients who are already in the ER, or patients who have been discharged from the hospital but have not paid their bills and are being held in the ER. This study aims to determine the experience of nurses in anticipating patient fluctuations in the emergency room at the Imelda Workers Indonesia General Hospital, Medan. The method used in this research is descriptive qualitative using a phenomenological approach. This research was conducted in the IGD RSU IPI Medan. The research process was carried out from March 2024 to August 2024. The sampling technique in this research was purposive sampling. In this research, there were 6 (six) participants who underwent in-depth interviews. This research uses the Colaizzi method to analyze data. The research results obtained were that there were 4 themes produced including expressions of nurses' feelings, inhibiting factors, supporting factors and solutions. For hospital institutions, especially the management department, to pay more attention to anticipating patient fluctuations in the ER, so that they have alternative solutions when facing patient fluctuations.